2005
DOI: 10.1021/jp050586h
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Dynamics in Amorphous Si3B3N7

Abstract: We present extensive numerical investigations of the structural relaxation dynamics of a realistic model of the amorphous high-temperature ceramic a-Si3B3N7, probing the mean-square displacement of the atoms, the bond survival probability, the average energy, the specific heat, and the two-point energy average. Combining the information from these different sources, we identify a transition temperature Tc approximately 2000 K below which the system is no longer ergodic and physical quantities observed over a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
3
14
0
2
Order By: Relevance
“…Thus, within the range of our simulations, the mean-field picture is only marginally appropriate for a quantitative description. This agrees with our earlier work [26,20] studying the glass transition: Judging from the specific heat curves, there appears to occur a considerable release of configurational entropy at temperatures far above the actual glass transition at T G ≈ 2000 − 2500 K that was computed based on the peak in the specific heat and the decrease of the diffusion constants.…”
Section: Cluster Size Distribution In the Fluid Phasesupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, within the range of our simulations, the mean-field picture is only marginally appropriate for a quantitative description. This agrees with our earlier work [26,20] studying the glass transition: Judging from the specific heat curves, there appears to occur a considerable release of configurational entropy at temperatures far above the actual glass transition at T G ≈ 2000 − 2500 K that was computed based on the peak in the specific heat and the decrease of the diffusion constants.…”
Section: Cluster Size Distribution In the Fluid Phasesupporting
confidence: 92%
“…We have investigated the stability of these void-containing structures [19] and have found that they should be kinetically stable up to ca. 1750 K. Above this temperature, a very slow transformation into a denser amorphous phase without larger voids should take place -the same phase one would also obtain if one could synthesize a-Si 3 B 3 N 7 via a glass transition from the melt [15] with a glass transition temperature somewhere in the range of 2000 -2250 K according to our simulations [20]. Up to now, however, the melt phase of Si 3 B 3 N 7 has not yet been accessible experimentally, most likely due to the evolution of N 2 from the melt.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…Angewandte Chemie time dependence is found for the slow improvement in energy during the aging process, as observed in long-time simulations for Si 3 B 3 N 7 models at temperatures below the melting point. [85] The effect of high pressures on the nanoporous material could have great ramifications for potential applications. [84] Constant-pressure (1-50 GPa) simulations at 300 K show that the system can be compacted significantly, and that much of the densification is irreversible.…”
Section: Amorphous Solidsmentioning
confidence: 99%